Exploring rationality in schizophrenia. Issue 1 (June 2015) - Revsbech, Rasmus; Mortensen, Erik Lykke; Owen, Gareth; Nordgaard, Julie; Jansson, Lennart; Sæbye, Ditte; Flensborg-Madsen, Trine; Parnas, Josef
Abstract : Background: Empirical studies of rationality (syllogisms) in patients with schizophrenia have obtained different results. One study found that patients reason more logically if the syllogism is presented through an unusual content. Aims: To explore syllogism-based rationality in schizophrenia. Method: Thirty-eight first-admitted patients with schizophrenia and 38 healthy controls solved 29 syllogisms that varied in presentation content (ordinary v. unusual) and validity (valid v. invalid). Statistical tests were made of unadjusted and adjusted group differences in models adjusting for intelligence and neuropsychological test performance. Results: Controls outperformed patients on all syllogism types, but the difference between the two groups was only significant for valid syllogisms presented with unusual content. However, when adjusting for intelligence and neuropsychological test performance, all group differences became non-significant. Conclusions: When taking intelligence and neuropsychological performance into account, patients with schizophrenia and controls perform similarly on syllogism tests of rationality.